Bridging Language Barriers: The Role of English Proficiency in Supporting Indonesian MSMEs’ International Success - Irfan Lantara (Lingedu: Journal of Linguistics and Education, 2025)
This study explores the significance of English language proficiency among Indonesian micro, small, and medium-sized enterprise (MSME) exporters, focusing on its role in enhancing international business success. Employing a qualitative case study design, data were collected through semi-structured interviews with five MSME actors from South Sulawesi. Findings indicate that English proficiency enables cross-border communication, fosters customer trust, and supports business expansion. However, entrepreneurs face barriers such as vocabulary limitations, pronunciation challenges, and anxiety in real-time interactions. Recommendations include context-based English training tailored to business practices, mentorship programs, and technology-enhanced communication tools to bridge linguistic gaps.